(untitled) (Tempo e Argumento, 2011)
This article addresses the possibility of recreating the idea of a city as a collective project based on the impressions of the ongoing Medellin experience in Colombia. It has been able to create a new urban and citizen-based network due to a new conciliation project where culture is the driver.